On the benchmarking of multi-junction photoelectrochemical fuel generating devices. Issue 3 (9th February 2017) - May, Matthias M.; Lackner, David; Ohlmann, Jens; Dimroth, Frank; van de Krol, Roel; Hannappel, Thomas; Schwarzburg, Klaus
Abstract : We discuss benchmarking considerations for multi-junction solar fuel absorbers and investigate the effects of spectral shaping by catalyst nanoparticles on design criteria. Abstract : Photoelectrochemical solar fuel generation is evolving steadily towards devices mature for applications, driven by the development of efficient multi-junction devices. The crucial characteristics deciding over feasibility of an application are efficiency and stability. Benchmarking and reporting routines for these characteristics are, however, not yet on a level of standardisation as in the photovoltaic community, mainly due to the intricacies of the photoelectrochemical dimension. We discuss best practice considerations for benchmarking and propose an alternative efficiency definition that includes stability. Furthermore, we analyse the effects of spectral shaping and anti-reflection properties introduced by catalyst nanoparticles and their impact on design criteria for direct solar fuel generation in monolithic devices.